Unique and redundant roles of SOX2 and SOX17 in regulating the germ cell tumor fate. Issue 6 (1st November 2019) - Jostes, Sina V.; Fellermeyer, Martin; Arévalo, Lena; Merges, Gina E.; Kristiansen, Glen; Nettersheim, Daniel; Schorle, Hubert
Abstract : Embryonal carcinomas (ECs) and seminomas are testicular germ cell tumors. ECs display expression of SOX2, while seminomas display expression of SOX17. In somatic differentiation, SOX17 drives endodermal cell fate. However, seminomas lack expression of endoderm markers, but show features of pluripotency. Here, we use chromatin immunoprecipitation sequencing to report and compare the binding pattern of SOX17 in seminoma‐like TCam‐2 cells to SOX17 in somatic cells and SOX2 in EC‐like 2102EP cells. In seminoma‐like cells, SOX17 was detected at canonical (SOX2/OCT4), compressed (SOX17/OCT4) and noncomposite SOX motifs. SOX17 regulates TFAP2C, PRDM1 and PRDM14, thereby maintaining latent pluripotency and suppressing somatic differentiation. In contrast, in somatic cells canonical motifs are rarely bound by SOX17. In sum, only 12% of SOX17‐binding sites overlap in seminoma‐like and somatic cells. This illustrates that binding site choice is highly dynamic and cell type specific. Deletion of SOX17 in seminoma‐like cells resulted in loss of pluripotency, marked by a reduction of OCT4 protein level and loss of alkaline phosphatase activity. Furthermore, we found that in EC‐like cells SOX2 regulates pluripotency‐associated genes, most likely by partnering with OCT4. In conclusion, SOX17 (in seminomas) functionally replaces SOX2 (in ECs) to maintain expression of the pluripotency cluster. Abstract : What's new? Seminomas are germ cell tumors of the testis, which are frequent tumors of young men and characterized by features of pluripotency and maintenance of an undifferentiated state. Here the authors examine the genome‐wide binding of the transcription factor SOX17, known as a determinant of endodermal differentiation. They find that in seminomas SOX17 is not controlling cell differentiation but maintains latent pluripotency and germ cell identity. In consequence, loss of SOX17 induces extra‐embryonic differentiation, indicating the importance of SOX17 expression for seminoma cell fate.